Design and development of Alkali Pozzolan Cement (APC) - Kulasuriya, Chandana; Vimonsatit, Vanissorn; Dias, W.P.S.; De Silva, P. (ELSEVIER, 2014)
This paper describes the development of an environmentally friendly Alkali Pozzolan Cement (APC), anon-hazardous dry cement powder that incorporates a large percentage of fly ash but needs only ambient temperature curing in order to achieve strengths comparable to OPC controls. APC consists of fly ash, lime, an activator and OPC (a ‘scaffolding’ material). Scaffolding was the most statistically significant factor contributing to the compressive strength of APC paste specimens, compared to activation, age (3 days vs 28 days) and temperature (ambient vs 15 h at 60 °C). SEM, EDS and XRD investigations were employed to explain variations in strength.